GPIIB ALLELIC POLYMORPHISM AS A FACTOR ASSOCIATED WITH THE PROBABILITY OF IMMUNE THROMBOCYTOPENIA AND THE SEVERITY OF HEMORRHAGIC SYNDROME - I. I. Zotova; S. I. Kapustin; S. V. Gritsaev; N. V. Mineeva; I. I. Krobinets; Zh. Yu. Sidorova; S. S. Bessmeltsev; A. V. Chechetkin (Онкогематология)
Russian Scientific Research Institute of Hematology and Transfusiology under the Federal Medico-Biological Agency; 16 Vtoraya Sovetskaya St., 191024 Saint Petersburg, RussiaPolymorphism of platelet glycoproteins GPIIIa (T1565C), GPIba (T434C), GPIIb (T2622G) and GPIa (A1648G) genes, responsible for the formation of alloantigenic platelet systems HPA-1, -2, -3 and -5, in patients with chronic immune thrombocytopenia (ITP) and in control group (CG) was investigated. Among ITP patients, the proportion of homozygotes of the GPIIb 2622 GG (HPA-3b/3b) gene was more than 2 times higher than in CG: 23.9 % versus 11.4 % (odds ratio (OR) = 2.4, 95 % confidence interval (CI): 1.0–5.8, p = 0.05). The frequency of HPA-3a/3a (GPIIb 2622TT,843Ile/Ile) genotype was higher in ITP patients with 2–3rd degrees of hemorrhagic syndrome (HS): 55.6% versus 25.0% in the group with 0–1st degree of HS (OR = 3.8, 95 % CI: 1.3–10.7, p = 0.02). The obtained data suggest the effect of T2622G polymorphism GPIIb gene both on development of disease (2622 GG genotype), and on serious manifestations of HS (2622 TT genotype), which allows considering this polymorphism as unfavorable prognostic criterion in ITP patients.